VDC_100102370126.0X000001. Issue 3 (March 2018) - Heimroth, Jamie; Chen, Eric; Sutton, Erica
There are very few clinical studies that highlight a definitive and comprehensive guideline for the management of enterocutaneous fistulas. Most accepted guidelines are found in textbooks and are taken from expert advice and case reports. The goal of this review is to highlight advancements relevant to the management of enterocutaneous fistulas from the recent two to three years. Although strong evidence-based guidelines are lacking, the consensus is that a multidisciplinary team working with a clear treatment plan targeting multiple aspects of management can maximize patient outcomes.